Macrophage Plasticity in Reproduction and Environmental Influences on Their Function - Chambers, Megan; Rees, April; Cronin, James G.; Nair, Manju; Jones, Nicholas; Thornton, Catherine A. (Frontiers in Immunology, 2021)
Macrophages are key components of the innate immune system and exhibit extensive plasticity and heterogeneity. In the non-pregnant endometrium, they play a significant role in the cycling uterus and throughout gestation they contribute to various processes underpinning reproductive success including implantation, placentation and parturition. Macrophages are also present in breastmilk and impart immunomodulatory benefits to the infant. For a healthy pregnancy, the maternal immune system must adapt to prevent fetal rejection and support development of the semi-allogenic fetus without compromising host defence. These functions are dependent on macrophage polarisation which is governed by the local tissue microenvironmental milieu. Disruption of this microenvironment can affect macrophage phenotype and function and is linked to adverse obstetric outcomes, e.g. spontaneous miscarriage and preterm birth. Determining the cellular and molecular mechanisms controlling macrophage polarisation at the maternal-fetal interface and the role of this in pregnancy complications could support approaches to alleviating adverse pregnancy outcomes.